The Moderating Role of Leverage on Earnings Per Share, Company Size, Liquidity, and Activity on the Financial Performance of Manufacturing Companies in 2019-2024 - Ali Fikri; G. Gusni (Manunggal Halim Jaya, 2027)
This study aims to analyze the moderating effect of leverage on earnings per share, company size, liquidity, and activity on the financial performance of manufacturing companies in 2019-2024. This study uses a quantitative method with the help of the statistical program EViews 13.0. Data were collected using secondary data from the financial reports of manufacturing companies from to 2019-2024. The data analysis technique used a regression model, namely, the Panel Data Regression Moderating Variables approach. The results of this study indicate that earnings per share has a positive effect on company financial performance, company size has a positive effect on company financial performance, liquidity has no effect on company financial performance, and activity has no effect on company financial performance. The moderating impact of leverage has a significant negative effect on earnings per share on company financial performance, leverage moderation has a significant negative effect on company size on company financial performance, leverage moderation has no effect on liquidity on company financial performance, and leverage moderation has a significant positive effect on company activity on company financial performance.